Watch Your Tone: Social Conditions Modulate Singing Strategies. (9th October 2015) - Ronald, Kelly L.; Skillman, Tasha; Lin, Andy; Li, Qingling; Fernandez‐Juricic, Esteban; Lucas, Jeffrey R.; Koenig, W.
Abstract Bird song is typically depicted as a male singing a long‐distance signal to potentially unknown receivers to (1) deter males and (2) attract females. Nevertheless, many songbirds sing from close distances to a known receiver; males of these species may be under more intense selective pressure to modify their songs depending on the sex of the receiver in order to convey different motivational states (aggression versus courtship) to the different sexes. In a laboratory setting, we examined how receiver sex affected within‐song variation of the close‐range singing behavior in the brown‐headed cowbird (Molothrus ater). Although we know that cowbird song is influenced by flock composition, it is still unclear as to how the cowbird modifies his song based on social context. Using a cross‐correlation analysis of each male's different song types, we found that pairs of songs were significantly more dissimilar if they were directed to females compared with songs directed to males. We subsequently tested whether there were any consistent spectral or temporal patterns in the songs males gave to females versus to males. Our results lend support for the Motivational Structural Rules Hypothesis as songs directed toward males had higher entropy (i.e., harshness) than the same song type directed toward females. Our results suggest that cowbirds may have evolved the ability to alter multiple dimensions of their singing behavior based on receiver sex.